RESEARCH ON ONLINE MARKETING STRATEGY OF STRAWBERRY IN FARM - Wu, Tiefeng (Journal of Buddhist Education and Research (JBER), 2023)
With the continuous development of Internet technology and the gradual change of consumers’ consumption concept, online marketing of fresh agricultural products has attracted more and more attention. In this study, farmers’ self-produced and sold agricultural products were selected as the target, and strawberries on the farm line were taken as an example. The market segmentation, target market selection and market positioning of farmers’ self-produced and sold agricultural products were analyzed, and the product positioning and brand positioning of strawberries on the farm line were established. On the basis of marketing development strategy and market positioning, the online marketing combination strategy of farm grass mold was formulated.